Enhancing Neurology Clinic Operations through Agile Methodology: A Study on Medical Record Information System Development - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This research aims to evaluate the influence of Agile Methodology im-plementation in developing Electronic Medical Record Systems (EMRs) on enhancing operational efficiency in neurology clinics. The identified issue lies in the complexity of information management within neurol-ogy clinic environments, affecting the efficiency and accuracy of medi-cal information provision. Results indicate that the adoption of Agile Methodology in EMR development has a positive impact on neurology clinic operations. The contribution of this research lies in the profound understanding of the significance of adaptive development methods that respond to user needs, thereby enhancing operational efficiency and service quality in neurology clinics. Furthermore, this study pro-vides a foundation for further research in information technology de-velopment within healthcare contexts, emphasizing adaptability, re-sponsiveness, and user satisfaction.